Controlled observational study and economic evaluation of the effect of city-centre night-time alcohol intoxication management services on the emergency care system compared with usual care. Issue 7 (4th November 2020) - Moore, Simon; Young, Tracey; Irving, Andy; Goodacre, Steve; Brennan, Alan; Amos, Yvette
Abstract : Background: Alcohol intoxication management services (AIMS) provide an alternative care pathway for alcohol-intoxicated adults otherwise requiring emergency department (ED) services and at times of high incidence. We estimate the effectiveness and cost-effectiveness of AIMS on ED attendance rates with ED and ambulance service performance indicators as secondary outcomes. Methods: A controlled longitudinal retrospective observational study in English and Welsh towns, six with AIMS and six without. Control and intervention cities were matched by sociodemographic characteristics. The primary outcome was ED attendance rate per night, secondary analyses explored hospital admission rates and ambulance response times. Interrupted time series analyses compared control and matched intervention sites pre-AIMS and post-AIMS. Cost-effectiveness analyses compared the component costs of AIMS to usual care before with results presented from the National Health Service and social care prospective. The number of diversions away from ED required for a service to be cost neutral was determined. Results: Analyses found considerable variation across sites, only one service was associated with a significant reduction in ED attendances (−4.89, p<0.01). The services offered by AIMS varied. On average AIMS had 7.57 (mean minimum=1.33, SD=1.37 to mean maximum=24.66, SD=12.58) in attendance per session, below the 11.02 diversions away from ED at which services would be expected to be cost neutral. Conclusions: AIMSs have variable effects on the emergency care system, reflecting variable structures and processes, but may be associated with modest reductions in the burden on ED and ambulance services. The more expensive model, supported by the ED, was the only configuration likely to divert patients away from ED. AIMS should be regarded as fledgling services that require further work to realise benefit. Trial registration number: ISRCTN63096364 .